`(x^3)y - x(y^3) = 4` Find `dy/dx` by implicit differentiation.

Textbook Question

Chapter 2, Review - Problem 79 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

`(x^3)*y - x*(y^3) = 4`

differentiating

`3(x^2)*y + (x^3)*(dy/dx) - (y^3) - 3x(y^2)*(dy/dx) = 0`

`or, (dy/dx)*[(x^3)-3x(y^2)] = (y^3) - 3(x^2)y`

`or, dy/dx = [(y^3) - 3(x^2)y]/[(x^3)-3x(y^2)]`

``

We’ve answered 318,955 questions. We can answer yours, too.

Ask a question